Evaluation of platinum nanoparticles ecotoxicity using representatives of distinct trophic levels of aquatic biocenosis - Hlavkova, Daniela; Beklova, Miroslava; Kopel, Pavel; Havelkova, Barbora (Neuro endocrinology letters, 2019)
OBJECTIVES: The aim of this study was to clarify the influence of three different sizes of platinum nanoparticles on aquatic ecosystem and assess the toxic effect in term of particle size. Tests were conducted on organisms representing all trophic levels of the aquatic ecosystem, namely producers (duckweed Lemna minor), consumers (water fleas Daphnia magna) and decomposers (bacteria Vibrio fischeri). DESIGN: Experiments were carried out methodologically in accordance with the following standards: OECD 221 guideline (Lemna sp. Growth Inhibition test), OECD 202 guideline (Inhibition of the mobility of Daphnia magna) and ISO 11348-2 (Inhibitory effect of platinum nanoparticles on the light emission of Vibrio fischeri). RESULTS: The most toxic have been the smallest sized platinum nanoparticles for all tested organisms. The highest toxicity of all tested samples (Pt1, Pt2, Pt3) was observed in bacteria (30´EC50 = 135.47; 167.94; 254.64 µg.L-1), respectively. The lowest toxicity was recorded for Daphnia (48hEC50 = 405.74; 413.24; 514.07 µg.L-1), respectively. CONCLUSION: The ecotoxicity of platinum nanoparticles varies considerably according to the test organisms and particle size.
Keywords: Daphnia; společenstvo; Animals; Platinum; platina; kovové nanočástice; vztah mezi dávkou a účinkem léčiva; Water Pollutants; zvířata; Biota; Dose-Response Relationship, Drug; Aliivibrio fischeri; Metal Nanoparticles; látky znečišťující vodu